Financial Ratios, Capital Structure, and EVA Impact on IDX Food and Beverage Manufacturers 2019-2021 Performance - Handini, Sri (Journal of Business Management and Economic Development, 2024)
This study examines how financial ratios, capital structure, and economic value added (EVA) affect Indonesia Stock Exchange-listed food and beverage manufacturers' financial performance. The study examined 14 companies as a sample and used financial statements from the Indonesia Stock Exchange website as secondary data. Descriptive statistical tests, classical assumption tests, multiple linear analysis, and hypothesis tests using t, F, and determination coefficient tests are some ways that data can be analyzed. The study found that financial ratio negatively affects the financial performance of Indonesia Stock Exchange-listed food and beverage companies (t count -2.943 < t table 2.024, significance values 0.006 < 0.05). Capital structure variables do not significantly affect financial performance for Stock Exchange-listed food and beverage manufacturing companies (t-calculus 0.728 < t-table 2.024, significance values 0.471 > 0.05). Economic value added (Eva) doesn't significantly affect companies that make food and drinks listed on the Indonesia Stock Exchange, as shown by t count -1.217 < t table 2.024 and significance value 0.231 > 0.05. Food and drink companies listed on the Indonesia Stock Exchange can make more money thanks to financial ratio, capital structure, and Eva. This is backed up by F count 4.096 > There are significance levels of 0.013 and 0.05 in F table 3.24. The independent variable in this study explains 18.5% of the company's financial performance.